“Who am I” Understanding Gender as a Strategy Prevention of LGBT in Islamic Boarding Orphanages - Sulastri, S; Dewi, Enita; Purwanto, Setiyo; Yuniartika, Wachidah (Universitas Muhammadiyah Surakarta, 2022)
Educational institutions that cannot be separated from the existence of homosexual issues are Islamic boarding schools Parents, orphanage administrator, and chaplains must recognize the development of their students who are entering the adolescent phase. Adolescence is a transitional phase to adulthood that needs attention. This phase can cause various problems regarding adolescent reproduction including taking actions that are included in the LGBT (Lesbian, Gay, Bisexual and Transgender) category. The community service activity aims to increase understanding of gender in adolescents (student) as a strategy in preventing LGBT. The methods used in this activity include health education, group discussion forums, mentoring, and program evaluation. The results of the service obtained increased knowledge and understanding of orphanage administrator, chaplains, parents and students in preventing LGBT at the Wisma Asuhan Yatim Nurul Huda. The incidence of LGBT in Islamic boarding schools can be prevented by various efforts, including increasing gender knowledge during adolescence, so that teenagers can understand who they are and how to behave.